2004
DOI: 10.1148/radiol.2333040031
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial and Nonbronchial Systemic Arteries at Multi–Detector Row CT Angiography: Comparison with Conventional Angiography

Abstract: Multi-detector row helical CT angiography provides more precise depiction of bronchial and nonbronchial systemic arteries than does conventional angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
123
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(154 citation statements)
references
References 38 publications
12
123
0
13
Order By: Relevance
“…If the bronchial artery originates from the descending aorta with a level of the fifth or sixth thoracic vertebra, it is called as orthotopic; when its origin is at the descending aorta other than at the expected site, at the aortic arch, or at any aortic collateral vessel, with an intrapulmonary course along the ma- jor bronchi, it is called as ectopic [6] . The most frequent origins of ectopic bronchial arteries were the concavity of the aortic arch (92/124; 74%) [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the bronchial artery originates from the descending aorta with a level of the fifth or sixth thoracic vertebra, it is called as orthotopic; when its origin is at the descending aorta other than at the expected site, at the aortic arch, or at any aortic collateral vessel, with an intrapulmonary course along the ma- jor bronchi, it is called as ectopic [6] . The most frequent origins of ectopic bronchial arteries were the concavity of the aortic arch (92/124; 74%) [7] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand non bronchial systemic arteries were defined as arteries that enter the parenchyma through the inferior pulmonary ligament or through the adherent pleura; their course is not parallel to that of the bronchi [6] . There are similar cases regarding different types of ectopic bronchial artery in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Remy-Jardin et al (36) demonstrated that MDCTA provides more detailed depiction of bronchial and nonbronchial systemic arteries than DSA.…”
Section: Multidetector Ctmentioning
confidence: 99%
“…A MDCTA of the chest performed before treatment is of value because the number and the origin of bronchial arteries may be carefully evaluated and the coexistence of an additional nonbronchial arterial supply may be easily depicted to determine the optimal angiographic approach (4,36). Recognition of more than one arterial supply before endovascular treatment in patients presenting with massive hemoptysis, will assist in choosing ectopic vessels amenable to embolization and in preventing recurrences of hemoptysis after initial successful embolization (15).…”
Section: Multidetector Ctmentioning
confidence: 99%
“…Compared to a conventional X-ray, the added value of contrast-enhanced multidetector CT (MDCT) systems, optionally equipped with EKG triggering to minimize pulsation artifacts of the thoracic vessels consists in improved detection of bronchiectasis (in cases of COPD or CF), bronchial carcinoma, aspergilloma [62,72], pulmonary arteriovenous malformations (PAVM) as well as aneurysms of the thoracic or pulmonary arteries. MDCT also provides useful information regarding the anatomy, origin and course of the bronchial arteries as well as the course of aberrant bronchial arteries [73,74]. Improved visualization of pulmonary pathologies and surgical planning can be achieved using numerous post-processing techniques such as multiplanar reconstruction (MPR), maximum intensity projection (MIP) or 3-dimensional (3 D) volume and surface displays (shaded surface display (SSD)).…”
mentioning
confidence: 99%